Education and Character Building: Ethical Aspects of Learning from Al-zarnūjī’s Ta‘līm Al-Muta‘allim - Tumin Tumin; Ahmad Faizuddin (Universitas Islam Negeri Mataram, 2017)
Character building is important for every Muslim as the Prophet Muhammad SAW was sent to perfect the character (akhlāq). An attempt to instilling good characters, Islamic education should focus on two main issues, i.e. the content of knowledge and the methodology for imparting the knowledge. Muslim scholars have proposed the concept of knowledge in Islamic education. One of them is Imam al-Zarnūjī. He developed the basic principles of education in Islam and his teaching methodology which has been widely used in educational institutions and learning in the Muslim world. This article examines the ethical aspects of learning from al-Zarnūjī’s monumental work, Ta‘līm al-Muta‘allim Ṭarīq al-Ta‘allum, including intention (niyah), seriousness (jidd), respect (ta‘ẓim), and trust in Allah (tawakkul). Using the method of content analysis, this study argues that according to al-Zarnūjī, knowledge is a means for character building. The ethical aspect of learning as proposed by al-Zarnūjī is significant for the advancement and perfection of both individual and the society in this world and the Hereafter. Thus, teaching and learning in Islam put emphasis on knowledge understanding, ethical values and character building to produce good human beings (al-insān al- ṣālih).